The Mediating Role of Adolescent-Parent Conflict in The Relationship Between Academic Procrastination, Personality Traits, and Identity Styles in Adolescents - Abdolahi, Mina; Salehyan, Maryam (International Journal of Education and Cognitive Sciences, 2022)
Purpose: Academic procrastination or procrastination is a common problem in the educational system, referring to the prevalent tendency of learners to delay performing assignments and academic activities to the extent that it alters the individual's effective performance. The study investigates the mediating role of adolescent-parent conflict in the relationship between academic procrastination, personality traits, and identity styles in adolescents. Methodology: This applied research, conducted through a descriptive survey methodology, involved a sample of 375 out of 16,347 high school students from Tehran's districts 5 and 22, selected via stratified random sampling. Data were gathered using standardized questionnaires on academic procrastination (Solomon & Rothblum, 1984), personality traits (NEO-FFI by Costa & McCrae, 1992), identity styles (Berzonsky, 1989), and adolescent-parent conflict (short version for adolescents by Prinz et al., 1979), validated for content validity and reliability with Cronbach's alpha coefficient. Structural equation modeling and software SmartPLS version 2 and SPSS version 19 were used to test hypotheses. Findings: Results indicated significant negative relationships between academic procrastination and adolescents' personality traits and identity styles, and positive relationships between personality traits and identity styles. Adolescent-parent conflict was found to mediate the relationship between academic procrastination and both personality traits and identity styles in adolescents. Conclusion: In conclusion, this research not only advances our theoretical understanding of academic procrastination but also suggests practical implications for educators, parents, and policymakers aiming to support adolescents' academic and personal development. Future research should continue to explore the multifaceted nature of procrastination, particularly in relation to family dynamics and educational settings, to develop more effective interventions and support mechanisms.